Intra complex recovery intervals for acute lower body post activation potentiation in elite badminton athletes - Lim, J. J.; Barley, C. I.; Chua, Y. J. (Journal of Athletic Enhancement, 2016)
1.1 Objectives: This study examined the acute effects of back squats on jump performance with a focus on the individual recovery interval for postactivation potentiation (PAP) through a discontinuous time course.